2019
DOI: 10.3390/ijerph16245046
|View full text |Cite
|
Sign up to set email alerts
|

The Temporal and Spatial Evolution of Marathons in China from 2010 to 2018

Abstract: The purpose of this study is to explore the spatial distribution pattern and influencing factors of the Chinese marathon. Geographic Information System (GIS) related spatial analysis tools were used to calculate the following-averaged nearest neighbor index, nuclear density analysis and hot spot analysis among others. The spatial distribution evolution characteristics and the influencing factors of eighteen Chinese marathon events in 2010, 129 in 2015 and 342 in 2018 were analyzed. The results show that (a) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 31 publications
(31 reference statements)
5
20
0
Order By: Relevance
“…Similar results can be shown in shorter 80-km ultra-marathons, where a decrease of performance gap began in 1985 [14]. In an analysis of ultra-marathons of varying lengths, women were also able to reduce the performance gap to men in 6, 72, 144, and 240 h races since 1975 [15], in 24 h races since 1998 [11], and over all decades in 50-km ultra-marathons worldwide [25].…”
Section: Performance Gap Disappeared Since 1990supporting
confidence: 76%
See 1 more Smart Citation
“…Similar results can be shown in shorter 80-km ultra-marathons, where a decrease of performance gap began in 1985 [14]. In an analysis of ultra-marathons of varying lengths, women were also able to reduce the performance gap to men in 6, 72, 144, and 240 h races since 1975 [15], in 24 h races since 1998 [11], and over all decades in 50-km ultra-marathons worldwide [25].…”
Section: Performance Gap Disappeared Since 1990supporting
confidence: 76%
“…This decline of participants in particular single events could be a result of an increasing number of events. An increase in events could also be shown in other long-distance events such as the marathons in China [25]. In our study, such a strong increase of 100-km ultra-marathon events could be demonstrated, especially in the last decade from 2010 to 2019.…”
Section: Ratio Participants/eventsupporting
confidence: 76%
“…Future research can also explore the impact of China's cultural environment on the holding of marathon events. From 2010 to 2018, the spatial distribution of marathon events in China can be found that, in addition to natural environmental resources, the cultural environment (population, policy, economy) also has a great impact on the holding of marathon events [62]. At the same time, the research ideas can also be applied to other countries, or even the world's famous marathon distribution research, and extend the findings from the present study.…”
Section: Limitations and Future Researchsupporting
confidence: 69%
“…After the Chinese government streamlined the administration of sports events, cities no longer need national approval to host marathons, and more cities have the freedom of choice to host marathons [62]. But after those lousy marathons, more cities may need to hold back.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Zuo et al took the lead in exploring the spatial distribution characteristics of Chinese marathon events. The size of urban populations; living standards; and the overall quality of urban residents (including the concept of sports and leisure), the social environment, and other social mechanism factors affect the spatial distribution of marathon events [7]. Additionally, the spatial distribution characteristics of Chinese marathon events are investigated based on the perspective of natural resources [8].…”
Section: Introductionmentioning
confidence: 99%